Impacts of tropical cyclones on extreme precipitation and flooding in a humid subtropical inland basin of China - Huishan Chen; Longfei Han; Yuying Tang; Juan Chen; Chaogui Lei; Xichun Li (Journal of Hydrology: Regional Studies)
Study region: Xiangjiang basin, a humid subtropical inland region of central-south China. Study focus: Tropical Cyclones (TCs) usually cause extreme precipitation events (EPEs) and flooding in both coastal and inland areas, resulting in severe economic losses. However, TC impacts in inland regions were seldom investigated. This study provided a climatological view of TCs, TC-induced EPEs and flooding in the Xiangjiang basin over the past nearly 70 years, and examined their relationships with ENSO using data from 127 meteorological stations, 22 hydrological stations, and TC tracks. New hydrological insights for the region: Xiangjiang basin averaged five TC visits annually, primarily between July and September, when the majority of EPEs and flooding associated with TCs occurred. Despite the relatively low frequency (less than 30 %) of TC-induced EPEs and flooding compared to coastal regions, their magnitudes were comparable to or even exceeded those in coastal regions. These influences were modulated by ENSO. In neutral years, the frequency and magnitude of TC-induced EPEs were greatest due to higher TC track density and frequency. Also, TC tracks shifted westward, increasing the likelihood of extreme TC flooding in neutral years. The southeast of the basin faced the highest risk of TC-related disasters, especially in neutral years. This paper highlights the need to strengthen monitoring and prevention for TC-induced disasters in inland regions.